Use and resource areas of audiovisual media in hospitals - Weibel, Ann (My University, 1971)
The study involved some exploration of the various audiovisual aids that are currently available and also how these various media are being utilized in educational endeavors in medical facilities. The research data was secured through a mailed survey instrument, initially to a pilot sample of six hospitals, selected as two private, two university hospitals and two county or Veterans' Administration institutions. Five out of the six questionnaires were returned. Then survey questionnaires were sent to 50 more hospitals selected at random, being careful to choose representatives of both public and private institutions, varying sizes ranging from medium sized to large county institutions, and located in all geographic areas of the United States. The survey questionnaire was addressed to the administrator of the hospital who then routed same to the persons involved. The pilot study was conducted from January 15, 1971 to February 15, 1971 and the actual survey from February 15, 1971 to March 22, 1971. An 80% response was obtained by March 15. An additional 15 letters and questionnaires were dispatched on March 16 and by March 22 a 100% response, or 50 hospitals, had answered. Analysis of the data was then done relating to the following items: 1. Types of hospitals involved 2. Hospital size range according to beds 3. Number of hospitals which had special A-V departments with employees and special funds allocated 4. Types of audiovisual aids used 5. Aids which were most popular 6. Types of approved training programs conducted 7. Areas and departments making use of the audiovisual aids. Tables were constructed to illustrate the above items. Analyses and results revealed that all but one hospital did employ audiovisual aids in their various educational programs. The analyses showed that the most prevalently used aids were the slide projector, film projector, blackboards, tape recorder and overhead projector. Approved training programs were listed under 27 categories and 76 different departments were given as making use of the audiovisual aids. Seventeen out of the 50 hospitals did have a separate audiovisual department with an aggregate of 69 persons employed in these departments and a budget, as specified by four hospitals, of a total sum of $123,500.00.
Keywords: Audio-visual education; Hospitals -- Audio-visual aids